Adapted Fuzzy Integral: An Application in the Finite Element Method - Sánchez, Daniel; Bassani, Luana T.; Barros, Laécio C.; Esmi, Estevão (Trends in Computational and Applied Mathematics, 2018)
In this paper we study and define an adapted fuzzy integral, based on the Sugeno integral. Moreover, we present a numerical integration formula which approximates the value of the adapted fuzzy integral. Thus, we prove that the Riemann integral and the adapted fuzzy integral are equivalent for power functions. Next, we apply the formula proposed in the numerical integration, required in the finite element method, to obtain a numerical solution of a boundary value problem for the one-dimensional Poisson equation. Finally, we observed better results of the approximate solution obtained in the example with the use of our formula when compared with the simple trapezoidal rule.